Co-hydrothermal carbonization of cellulose, hemicellulose, and protein with aqueous phase recirculation: Insight into the reaction mechanisms on hydrochar formation. (15th July 2022) - Liu, Tonggui; Jiao, HuiTing; Yang, Longsheng; Zhang, Weijin; Hu, Yingbing; Guo, Yonghao; Yang, Lihong; Leng, Songqi; Chen, Jiefeng; Chen, Jie; Peng, Haoyi; Leng, Lijian; et al.
Abstract: Co-hydrothermal carbonization (Co-HTC) coupled with aqueous phase (AP) recirculation has huge potential to improve hydrochar production. In this study, three model compounds, namely wheat straw cellulose (cellulose, Ce), xylan (hemicellulose, He), and soya-protein (protein, Pr), were processed by HTC individually or Co-HTC in combination, with or without AP recirculation. Hydrochar formation behavior was investigated through analysis of hydrochar and AP by elemental analysis, X-ray photoelectron spectroscopy (XPS), Pyrolyzer-gas chromatography-mass spectrometry (Py-GC-MS), GC-MS, and a series of other characterizations. Elemental compositions reveal that both Co-HTC and AP recirculation promoted hydrochar formation and reduction of oxygen in hydrochar, and the combination promoted these effects. Furthermore, XPS and Py-GC-MS results show that the building blocks of hydrochar were oxygenated compounds from Ce and He such as furans and furfurals, and nitrogen-containing compounds from Pr such as amino acids and N-heterocycles. Subsequently, hydrochar formation mechanisms were proposed by results from GC-MS analysis of AP and the above observations. The major mechanisms account for enhanced hydrochar formation during Co-HTC with AP recirculation were Maillard reaction occurred between amino acids and saccharides, catalytical effects (mainly on Maillard reaction) from acids in the recycling AP, and the repolymerization or condensation of accumulated compounds in AP. Graphical abstract: Image 1 Highlights: Co-HTC of models coupled with aqueous phase (AP) recirculation was investigated. Promoting effects on hydrochar formation and oxygen reduction were achieved. Short-chain acids were the main reason for the enhanced hydrochar yield. Further enhancement on Maillard reaction was observed during AP recirculation. Numerous compounds accumulated in AP were verified accounting for HTC mechanisms.